Secondary Metabolites Screening Using GC-MS and In-Vitro Biological Assessment Against Human Pathogenic Bacterial Strains of Viola Indica - Ullah, Rahim; Suleman, Muhammad; Nawaz, Naik; Niaz, Aiman; Ahamd, Kashif (Journal of Chemistry and Environment, 2024)
Viola indica, a medicinal herb with a long history of traditional use in treating various diseases. In this study we analyzed methanolic extract of Viola indica for metabolite composition using GC-MS, and antibacterial activity through disc diffusion method. In GC-MS analysis, we found total of 25 metabolites in which the major metabolites were 9,12-Octadecadienoic acid (Z,Z)- (20%; 20.34 min), followed by Stigmasterol, 22,23-dihydro- (16%; 26 min) and α-Amyrin (12.38%; 26.65 min) . In antibacterial activity viola indica methanolic extract showed significant antibacterial effects against all bacterial strains. The highest antibacterial activity was recorded against Bacillus subtilis (8.50±0.20 mm), followed by Klebsiella pneumoniae (8.10±0.25 mm) zone of inhibition, while the lowest was recorded against Staphylococcus aureus (2.10±0.30 mm). The result of this study suggests that viola indica has potent antibacterial metabolites with good potential as a natural alternative to synthetic antibacterial agents. However, this study also suggest that more instrumental and biological research is required to explore it’s in-depth phytochemistry, pharmacological potential and toxicological properties.